Synopsis and Review: Algebraic Quantum Theory of Consciousness by Elio Conte (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Algebraic Quantum Theory of ConsciousnessA Solution to the Problem of Quantum Collapse in Systems Having Three Anticommuting ElementsISBN 978-88-255-1707-1, formato 17 x 24 cm, 112 pagine, 14 euro